Challenges Of Public Educational Institution Management By The Head Of The Institutions In Assam - Sinha, Suhrid; Sinha, Subhash; Sinha, Juli (International Journal of Psychosocial Rehabilitation, 2020)
Education is the tool that enlightens a person with knowledge to lead their life in a meaningful and worthwhile way that is also beneficial for society and humanity. The teacher is the backbone of society and is also called the social engineer. With the current demands and educational needs, the process of education and learning generally takes place on a school campus in a formal mode of learning. Hence, the responsibility of managing that school or educational institution has to be on someone’s shoulder and that person is a teacher of that institution, irrespective of the level of education. In this study, different roles and responsibilities of the head of institutions and some issues and challenges related to the management of educational institutions are discussed thoroughly, and based upon the study, some needful and useful suggestions are also given to lower the load of the teachers envisaged under the responsibility of the heads of institutions.